1972
DOI: 10.1111/j.1399-3054.1972.tb03605.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Exogenous Growth Inhibitors and Endogenous Levels of Ethylene, and Tuberization of Dahlias

Abstract: Treatments with abscisic acid (ABA), succinic acid‐2,2‐dimethylhydrazide (SADH), or 2 chlorethyl phosphonic acid (ethephon) promoted the tuberization of dahlia plants in long‐days. This effect was smaller, however, than the effect short days have on tuberization. In contrast, gibberellic acid (GA) treatments inhibited tuberization. SADH and ethephon treatments of budless leaf‐cuttings inhibited tuberization whereas ABA treatments slightly enhanced it. Evolution of endogenous ethylene reached a peak between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 9 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…Thus high soil N levels and gibberellin, which promote shoot growth, tend to reduce tuber growth, while treatments which inhibit or reduce shoot growth, such as treatment with chlorocholine chloride, promote growth of the tubers. Biran et al (1) proposed that short days promote the formation of tuberous roots in dahlia through inhibition of top growth and consequent diversion of assimilates to the root. The implication of their hypothesis is that daylength controls tuberization only if an alternate "sink" is present.…”
Section: Discussionmentioning
confidence: 99%
“…Thus high soil N levels and gibberellin, which promote shoot growth, tend to reduce tuber growth, while treatments which inhibit or reduce shoot growth, such as treatment with chlorocholine chloride, promote growth of the tubers. Biran et al (1) proposed that short days promote the formation of tuberous roots in dahlia through inhibition of top growth and consequent diversion of assimilates to the root. The implication of their hypothesis is that daylength controls tuberization only if an alternate "sink" is present.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Torres and Gomez-Campo (6) reported an increase in the number of tubers per plant at harvest in response to Ethephon' solutions applied to the soil. Biran et al (2) (14) showed that Ethephon did not promote tuber formation in potato stolons cultured in vitro.…”
mentioning
confidence: 99%
“…In dahlia it has been shown that there are changes in endogenous levels of ethylene which correlate with tuberization (Biran et al 1972); however, this has not been reported in potato. Indole-3-acetic acid (JAA) has been shown to increase in the leaves of potato plants when the roots were exposed to high levels of CO 2 in order to induce the tuberization process (Arteca et al 1980), and it has since been suggested that JAA may play an important role in the tuberization process (Melis and van Staden 1984).…”
Section: Other Plant Growth Substancesmentioning
confidence: 91%